2022
DOI: 10.3389/fendo.2022.1058101
|View full text |Cite
|
Sign up to set email alerts
|

Understanding gut-liver axis nitrogen metabolism in Fatty Liver Disease

Abstract: The homeostasis of the most important nitrogen-containing intermediates, ammonia and glutamine, is a tightly regulated process in which the gut-liver axis plays a central role. Several studies revealed that nitrogen metabolism is altered in Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD), a consensus-driven novel nomenclature for Non-Alcoholic Fatty Liver Disease (NAFLD), the most common chronic liver disease worldwide. Both increased ammonia production by gut microbiota and decreased ammonia hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Here, we discovered that empagliflozin attenuated the liver fibrosis induced by HFD/STZ, which is consistent with the reports in previous studies. 9,18 Combined with the promoting effect of intestinal flora on liver fibrosis 19 and the alleviating effect of empagliflozin on liver fibrosis, 20 we further explored the potential mechanism and revealed that empagliflozin altered the intestinal flora of liver fibrosis. More importantly, further data revealed that Lactobacillus, Ruminococcus and Adlercreutzia might be the vital microbiota for empagliflozin to improve liver fibrosis in HFD/STZ-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we discovered that empagliflozin attenuated the liver fibrosis induced by HFD/STZ, which is consistent with the reports in previous studies. 9,18 Combined with the promoting effect of intestinal flora on liver fibrosis 19 and the alleviating effect of empagliflozin on liver fibrosis, 20 we further explored the potential mechanism and revealed that empagliflozin altered the intestinal flora of liver fibrosis. More importantly, further data revealed that Lactobacillus, Ruminococcus and Adlercreutzia might be the vital microbiota for empagliflozin to improve liver fibrosis in HFD/STZ-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 For example, intestinal microbial metabolites alter host gut mucosal proteins and lead to liver injury. 53 Endogenous changes in the gut affect the intestinal barrier and promote intestinal inflammation. 54 Besides, intestinal-associated lymphoid tissue participates in intestinal barrier function and prevents intestinal inflammation.…”
Section: Mechanisms Linking the Gut-liver Axismentioning
confidence: 99%